New Perspective of Calcium Oxide Nanoparticles in Forensic Science: Dr. Syeda Mona Hassan, Dr. Aftab Ahmad Malik, Hafiza Hadia Shehzad - DR Syeda Mona Hassan; Dr. Aftab Ahmad Malik; Hafiza Hadia Shehzad (International Journal for Electronic Crime Investigation, 2022)
Nano-technologies have wide applications in the field of forensic science. Nanotechnology is animportant and powerful tool in most the areas including medicine, imaging, and forensic sciences. Ithas potential to make significant positive contribution in forensic science in crime detection. Thepresent article focuses on the applications of CaO nanoparticles in developing and detecting thelatent fingerprints. Fingerprint is considered noteworthy evidence in any crime scene, andnano-based techniques. An attempt was made to elucidate how nanotechnologies could be crucial inaddressing current forensic investigation issues such as explosive detection, toxicological analysis,finger print analysis, forensic DNA analysis, detection of explosive residue, forensic nano trackersand drug facilitated crime.